PERSEPSI MASYARAKAT TERHADAP LUBUK LARANGAN SEBAGAI KEARIFAN LOKAL DALAM PENGELOLAAN SUNGAI DI NAGARI RABI JONGGOR, KECAMATAN GUNUNG TULEH, KABUPATEN PASAMAN BARAT - Sintia Rahamadani; Endah Purwaningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the strengthening of local wisdom in Fish Lubuk Larangan as a strategic instrument in the management and conservation of river ecosystems in Nagari Rabi Jonggor, West Pasaman Regency. Using a mixed method approach with a sequential explanatory scheme, this study integrates field observations of the river's physical characteristics, structured questionnaires to 60 respondents, and in-depth interviews with traditional stakeholders and the village government. The results of the physical analysis indicate that the river's characteristics strongly support a fisheries ecosystem, with an average width of 10.67 meters and a current speed of 0.27 m/s. From a socio-ecological perspective, community perception of the existence of Lubuk Larangan is in the high to very high category. This is reflected in the community's high positive attitude (average 4.38), strong socio-cultural dimensions based on customary institutions (average 4.17), and a good level of knowledge of regulations (average 4.03). Although it does not provide short-term economic needs that trigger minor violations, the agreement on customary sanctions remains the main protector of river sustainability. This study concludes that optimizing river governance based on local wisdom requires strengthening the legality of customary institutional sanctions in synergy with village government policies to ensure ecological sustainability and community welfare.